2021
DOI: 10.1182/bloodadvances.2020003955
|View full text |Cite|
|
Sign up to set email alerts
|

Antagonism of inhibitors of apoptosis proteins reveals a novel, immune response-based therapeutic approach for T-cell lymphoma

Abstract: Tolinapant (ASTX660) is a potent, non-peptidomimetic antagonist of cIAP1/2 and XIAP, which is currently being evaluated in a phase 2 study in T-cell lymphoma (TCL) patients. Tolinapant has demonstrated evidence of single agent clinical activity in relapsed/refractory peripheral T-cell lymphoma (PTCL) and cutaneous T-cell lymphoma (CTCL). To investigate the mechanism of action underlying the single agent activity observed in the clinic we have used a comprehensive translational approach integrating in vitro and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…The study protocol was approved by the Institutional Review Board or independent ethics committee prior to study initiation. Cytokine analysis was performed using the Human ExplorerMAP v. 1.0 (Myriad RBM), as described previously ( 11 ). Samples from the first two cycles of 63 patients with PTCL were analyzed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study protocol was approved by the Institutional Review Board or independent ethics committee prior to study initiation. Cytokine analysis was performed using the Human ExplorerMAP v. 1.0 (Myriad RBM), as described previously ( 11 ). Samples from the first two cycles of 63 patients with PTCL were analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…In an ongoing phase II trial (NCT02503423), tolinapant showed activity against extensively pretreated peripheral and cutaneous T-cell lymphomas (PTCL and CTCL; refs. 12, 13 ) and patient samples from this trial have demonstrated some preliminary evidence of immune modulation ( 11 ).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…A fragment with a millimolar activity (XIAP: IC 50 >5 mM, cIAP >5 mM) served as a starting point for development, [23] and they managed to generate low nanomolar compounds by means of structure‐based design [24] . Tolinapant/ASTX660 ( 2 , Figure 5, XIAP=3 nM; cIAP1=0.2 nM) was selected as the final clinical candidate that is currently being evaluated in a phase II study in T‐cell lymphoma patients [25] …”
Section: Medicinal Chemistry and Target Highlightsmentioning
confidence: 99%
“…[24] Tolinapant/ASTX660 (2, Figure 5, XIAP = 3 nM; cIAP1 = 0.2 nM) was selected as the final clinical candidate that is currently being evaluated in a phase II study in T-cell lymphoma patients. [25]…”
Section: Medicinal Chemistry and Target Highlightsmentioning
confidence: 99%